EVALUASI KINERJA PROFESIONALISME GURU TERHADAP ANAK DIDIK (Studi Di SMA Negeri 1 Samudera) - Saiful Bahri; Nurzamli Nurzamli; Abdul Mutaleb (Sekolah Tinggi Ilmu Administrasi Nasional, 2022)
The purpose of this study is to explain the performance evaluation of teacher professionalism toward students at SMA Negeri 1 Samudera, North Aceh, Indonesia, as well as the factors that become obstacles in efforts to improve teacher professionalism's performance toward students. This research is important to do because the phenomenon that occurs is that teachers are models for their students so students want to learn that a teacher must always introspect about what his students expect, and it is hoped that teacher professionalism must be improved. The research method used is the qualitative method. The data collection technique used is direct interviews and documentation or literature research. Findings reported that the evaluation of learning outcomes is carried out through observations during the implementation of the learning process and through monitoring, discipline in the learning process, and class mastery. Besides that, the inhibiting factors in increasing teacher professionalism at this school are a lack of mastery of the material, low knowledge about technology, and a lack of motivation. Other inhibiting factors for professional performance are low discipline, a lack of skills or arts in learning, and still low knowledge of technology.